Branched polysiloxane polymer and method for preparing high-adhesion and low-oiling organic silicone gel using the same

By using branched polysiloxane polymers and hydrogen-containing cross-linking agents for addition curing under the action of platinum catalysts, the problems of weak adhesion, serious oil separation and high allergy rate of silicone gel in the medical field are solved. , realizing a silicone gel with high adhesion and low oil bleeding, which is suitable for applications in the medical field.

CN118852629BActive Publication Date: 2025-01-17SHANDONG DONGYUE ORGANIC SILICON MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411348441.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-17
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Existing silicon gels are prone to problems such as poor bonding, serious oil dissipation and high allergic rates during bonding use, which affects their application in the medical field.

Method used

Using branched polysiloxane polymer as the main agent, it is added and cured with a hydrogen-containing cross-linking agent under the action of a platinum catalyst to form a silicone gel with high adhesion and low oil bleeding.

Benefits of technology

This method effectively reduces the oil separation rate, improves the adhesion between the silicone gel and the substrate and skin, enhances the peeling strength, is suitable for applications in the medical field, and is safe and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of organosilicon materials, and specifically to a branched polysiloxane polymer and a method for preparing a high-bonding and low-oiling organosilicon gel using the same. The branched polysiloxane polymer is prepared by reacting the following raw materials: a: a linear polysiloxane with a single-end hydroxyl structure, b: a polysiloxane with a trifunctional or tetrafunctional branched structure, and c: a hydroxyl- or vinyl-terminated linear polysiloxane; the method for preparing the high-bonding and low-oiling organosilicon gel is prepared from A: a branched polysiloxane polymer, B: an organohydrogen polysiloxane, C: a platinum-based catalyst, and D: an inhibitor. In the present invention, an isotropic linear polysiloxane and a branched polysiloxane are firstly reacted and connected through an active hydroxyl group to form a unique branched structure, and then the resultant silicone gel product is effectively reduced in oiling rate by addition curing with a hydrogen-containing crosslinking agent under the action of a platinum-based catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organosilicon materials, and in particular to a branched polysiloxane polymer and a method for preparing a high-bonding and low-oiling organosilicon gel by using the same. Background Art

[0002] Silicone material is a high-performance polymer material. It is widely used in medical, electronic, construction, automotive and other fields due to its excellent heat resistance, weather resistance, electrical insulation, biocompatibility and other properties. Among them, silicone gel is an important silicone material. It has good light transmittance, softness and elasticity. It is often used in electronic packaging, medical devices, wound care, contact lenses, sealing materials and other fields.

[0003] In the medical field, silicone gel can be used as an adhesive in many application scenarios due to its soft surface, good biocompatibility and low allergy rate. Such as medical device fixation, skin care, scar improvement, etc. However, during the use of silicone gel for bonding, the following phenomena often occur: when bonding with objects, the bonding is often not strong, and the silicone gel is easy to fall off the skin; the oil separation phenomenon is serious, which contaminates the wound and affects the healing of the wound; there is a lot of silicone residue, and large-scale transfer occurs. The occurrence of the above phenomena seriously affects the performance and use effect of silicone gel.

[0004] In order to solve the many problems existing in the above-mentioned silicone gel, the prior art usually adopts methods such as adding fillers and changing the structure of silicone gel. For example, by adding silica nanoparticles, the ability of silicone gel to resist oil precipitation can be improved, but it also brings new problems. The transparency and softness of silicone gel are affected, which affects its performance in certain applications; for example, by changing the molecular structure of silicone gel, the oil precipitation rate is reduced. For example, by adding a hydrogen-containing cross-linking agent, a silylation reaction can occur with the vinyl group in the silicone gel to form a stable three-dimensional network structure, thereby improving the peel strength of the silicone gel. However, with the increase of hydrogen-containing cross-linking agents, the hardness and softness of silicone gel decrease, affecting its performance. Finally, some solutions in the prior art may increase the allergy rate of silicone gel, limiting its application in the medical field.

[0005] In patent CN111918928A, a T-shaped branched chain organopolysiloxane having more than 3 alkenyl groups bonded to silicon atoms in one molecule at the end of the molecular chain is used as the main agent, and a silicone gel prepared by using hydrogen-containing silicone oil as a crosslinking agent has a free oil rate of less than 15%. However, although the method described in the patent can reduce oil precipitation to a certain extent, the loose branched chain structure makes it difficult for the silicone gel to show bonding properties, and the adhesion between the silicone gel and the substrate is poor, making it difficult to apply to the medical field. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a branched polysiloxane polymer as a main agent of an organic silicone gel, and the prepared organic silicone gel has a certain high peeling force while maintaining softness.

[0007] The invention also provides a method for preparing a high-adhesion and low-oiling organic silicon gel by using the same, which has a simple preparation process and reduces production costs.

[0008] The branched polysiloxane polymer of the present invention is prepared by reacting the following raw materials:

[0009] a: Linear polysiloxane with a single-terminal hydroxyl structure;

[0010] b: polysiloxane having a trifunctional or tetrafunctional branched structure;

[0011] c: hydroxyl- or vinyl-terminated linear polysiloxane; the molar ratio of a, b, and c is (3-50):1:(0-3).

[0012] The general structural formula of a is: 1 1R 2 1CH3SiO[SiCH3R 2 1O] X1 [Si(CH3)2O] Y1 Si(CH3)2OH;

[0013] The R 1 1 is any one of -Vi, -CH3, -OCH3; R 2 1 is any one of -CH3 and -Ph; X1 and Y1 are integers of 10-1000.

[0014] Preferably, the R 1 1 is any one of -Vi and -CH3, wherein R 2 1 is -CH3; X1 and Y1 are integers of 10-500.

[0015] The general structural formula of b is: 1 2] n SiO (4-n) / 2 ] q [SiCH3R 2 2O] X2 [Si(CH3)2R 1 2O ½ ] m1 [Si(CH3)2R 2 2O ½ ] m2 [OH] s ;

[0016] The R1 2 is any one of -Vi, -CH3, -OCH3; R 2 2 is any one of -CH3 and -Ph; X2 is an integer of 0-100, n is an integer of 0 or 1; m1 and m2 are integers of 0-100; q and s are integers of 5-50.

[0017] Preferably, the R 1 2 is any one of -Vi and -CH3, wherein R 2 2 is -CH3; X2 is an integer of 0-50, m1 and m2 are integers of 1-50, and q and s are integers of 5-30.

[0018] The general structural formula of c is: 3 (CH3)2SiO[Si(CH3)2O] X3 Si(CH3)2R 3 ;

[0019] The R 3 It is any one of -Vi and -OH, and X3 is an integer of 50-1600.

[0020] Preferably, X3 is an integer of 100-600.

[0021] The preparation method of the branched polysiloxane polymer is as follows: a, b and c are put into a reaction container, the temperature is increased, an alkali glue is added to react, and then an acid glue is added to neutralize to obtain the branched polysiloxane polymer.

[0022] The method for preparing high-adhesion and low-oiling silicone gel by using branched polysiloxane polymer of the present invention is prepared by reacting the following raw components:

[0023] A: branched polysiloxane polymer;

[0024] B: organohydrogenpolysiloxane;

[0025] C: platinum catalyst;

[0026] D: inhibitor;

[0027] The branched polysiloxane polymer has different structures and different vinyl contents. Therefore, when cross-linking and curing with organohydrogenpolysiloxanes of different hydrogen contents and different molecular weights, the ratio of the vinyl molar amount to the silicon hydrogen molar amount is maintained in the range of Si-Vi:Si-H=0.5-1.0, preferably Si-Vi:Si-H=1:(0.7-0.9), and is adjusted according to actual conditions.

[0028] The platinum catalyst is added in an amount of 1-100 ppm, calculated based on the platinum element content;

[0029] Any known platinum-based compound (platinum or platinum-containing compound) can be used as component C. Examples of component C include platinum fine powder, platinum black, chloroplatinic acid, alcohol-modified products of chloroplatinic acid, complexes of chloroplatinic acid and dienes, platinum-olefin complexes, platinum-carbonyl complexes such as chloroplatinic acid-divinyltetramethyldisiloxane complexes, chloroplatinic acid-tetravinyltetramethylcyclotetrasiloxane complexes, chloroplatinic acid-alkenylsiloxane complexes, platinum-divinyltetramethyldisiloxane complexes, platinum-tetravinyltetramethylcyclotetrasiloxane complexes, and complexes of acetylene acid and chloroplatinic acid. The above catalysts can be used alone or in a mixture of two or more. Preferably, the platinum-alkenylsiloxane complex.

[0030] The added amount of the inhibitor is 1-1000 ppm.

[0031] The method for preparing the high-adhesion and low-oiling organic silicone gel comprises the following steps: mixing A and B evenly, adding D and mixing evenly, and then adding C and mixing evenly to obtain the high-adhesion and low-oiling organic silicone gel.

[0032] The inhibitor is one of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol or 3,5-dimethyl-1-hexynyl-3-ol, or a mixture of more than one thereof.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention first connects the heterogeneous linear polysiloxane and the branched polysiloxane through reactive hydroxyl groups to form a unique branched structure, and then performs addition curing with a hydrogen-containing crosslinking agent under the action of a platinum catalyst to form a silicone gel product that can effectively reduce the oil separation rate. At the same time, the structure improves the adhesion between the silicone oil molecules and the substrate and the skin or medical equipment, thereby improving the peel strength, greatly enhancing the application effect of silicone gel in the medical field.

[0035] 2. The present invention does not directly increase the cohesive strength by adding cross-linking components such as coupling agents and polysilicone resins, thereby increasing the hardness of the silicone gel. While maintaining softness, it has a certain high peeling force and is more suitable for medical environments.

[0036] 3. The organic silicone gel of the present invention improves the oil separation rate and peel strength without adding other fillers and additives that may increase the allergy rate, and its application in the medical field is safer and more reliable. DETAILED DESCRIPTION

[0037] The present invention will be further described below with reference to the embodiments.

[0038] Unless otherwise specified, all raw materials used in the examples are commercially available.

[0039] The reaction raw materials used in the embodiments of the present invention, such as terminal hydroxyl silicone oil, octamethylcyclotetrasiloxane, and hexamethylcyclotrisiloxane, were purchased from Shandong Dongyue Silicone Materials Co., Ltd., methyl orthosilicate, methyltrimethoxysilane, and hexamethyldisiloxane were purchased from Qufu Chenguang Chemical Co., Ltd., and reagents such as KOH, phosphoric acid, acetic acid, tetrahydrofuran, methyl lithium, methanol, and tetramethylammonium hydroxide were purchased from Aladdin Reagent Network.

[0040] Example 1

[0041] Add 8.6g of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane and 200g of anhydrous tetrahydrofuran to a dry flask, protect with nitrogen, and cool to 0°C. Add 50ml of methyl lithium (2M in n-hexane) to the flask and keep the temperature at 0°C for 30min. Dissolve 1480g of hexamethylcyclotrisiloxane in 500ml of anhydrous tetrahydrofuran, add to the above flask, and react at 30°C for 5h. Add 6g of glacial acetic acid and react for 20min. Filter to remove insoluble salts. At 30°C and -0.095MPa, remove tetrahydrofuran from the system to obtain a single-end hydroxyl single-end vinyl polydimethylsiloxane product with a chain number of 200: Vi(CH3)2SiO[Si(CH3)2O] 200 Si(CH3)2OH——

Chemistry 1

[0042] 45.7g of methyl orthosilicate, 19.4g of hexamethyldisiloxane, 14.8g of octamethylcyclotetrasiloxane, 5.7ml of methanol and 40ml of toluene were added to a flask, fully mixed and stirred, and the temperature of the mixed solution in the flask was reduced to 10°C. 43.2g of a 0.5%wt aqueous hydrochloric acid solution was added dropwise to the above flask using a constant pressure dropping funnel. The addition was completed in 100 minutes, and the temperature in the reaction flask was maintained at 15°C. The temperature was raised to 65°C and refluxed for 2h, then cooled to 25°C, allowed to stand for stratification, the lower layer of acid water was separated, and the upper layer of oil phase was removed from the system at 90°C and -0.095MPa to obtain MDQ polysiloxane with a tetrafunctional branched structure (where "M, D, Q" represent "SiR1R2R3O ½ "monofunctional", "SiR1R2O" difunctional, "SiO2" tetrafunctional structure of silicon-oxygen chain. M / D / Q = 24:20:30, and 1 mol MDQ molecule contains about 5 mol hydroxyl active groups.): [SiO2] 30 [Si(CH3)2O] 20 [Si(CH3)3O ½ ] 24 [OH]5——[Chemistry 2];

[0043] Preparation of the high-adhesion and low-oiling silicone gel:

[0044] A: Add [Chemical 1] and [Chemical 2] in a molar ratio of 5:1 into a four-necked bottle equipped with a thermometer and a stirrer, heat to 150°C, add 40 ppm of KOH catalyst, react under vacuum for 4 hours, add 40 ppm of phosphoric acid, stir and neutralize for 1 hour to obtain "branched polysiloxane polymer 1", which is used as component A for preparing high-adhesion and low-oiling silicone gel.

[0045] B: Add 12g of tetramethylcyclotetrasiloxane, 13.4g of tetramethyldisiloxane, 370g of octamethylcyclotetrasiloxane and 7.9g of concentrated sulfuric acid into a flask, stir and react at 25℃ for 5h, add 12.0g of sodium carbonate powder and stir to neutralize, filter out the insoluble solid powder, remove the low molecular weight in the filtrate from the system at 120℃ and -0.095MPa, and obtain a hydrogenated linear polysiloxane with 50 chain segments, two ends capped with dimethylhydrogensiloxy groups and two silicon-hydrogen chain segments in the middle: H(CH3)2SiO[Si(CH3)2] 50 [SiHCH3O]2Si(CH3)2H——[Chemical 3];

[0046] C: chloroplatinic acid-divinyltetramethyldisiloxane complex containing 5000 ppm of platinum atoms;

[0047] D: 1-ethynyl-1-cyclohexanol;

[0048] Mix A and B evenly, add D and mix evenly, then add C and mix evenly to obtain a high-adhesion and low-oiling silicone gel.

[0049] The peel strength, cone penetration and oil separation rate of high-bonding and low-oil separation silicone gel were tested according to the above test method. The specific addition amount and test results are shown in Table 1.

[0050] Example 2

[0051] 76.4g of methyl orthosilicate, 28.4g of hexamethyldisiloxane, 5.7ml of methanol and 40ml of toluene were added to a flask, mixed and stirred thoroughly, and the temperature of the mixed solution in the flask was lowered to 10°C. 72.0g of a 0.5%wt aqueous hydrochloric acid solution was added dropwise to the flask using a constant pressure dropping funnel. The addition was completed over 100 minutes, and the temperature in the reaction flask was maintained at 15°C. The temperature was raised to 65°C and refluxed for 2h, then cooled to 25°C, allowed to stand for stratification, the lower acid water was separated, and the upper oil phase was placed at 90°C and -0.095MPa to remove the low-boiling substances from the system to obtain MQ with a tetrafunctional branched structure (indicating that it has "SiR1R2R3O½ ” structure with a monofunctional “M” chain segment and a tetrafunctional “SiO2” structure with a “Q” silicon-oxygen chain segment, where M / Q=35:50. At the same time, 1 mol MQ polysiloxane contains about 6 mol of hydroxyl active groups.) Polysiloxane: [SiO2] 50 [Si(CH3)3O ½ ] 35 [OH]6——[Chemical 4];

[0052] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0053] a:Vi(CH3)2SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 1];

[0054] b: [SiO2] 50 [Si(CH3)3O ½ ] 35 [OH]6——[Chemical 4];

[0055] A: Add the above-mentioned [Chemical 1] and [Chemical 4] in a molar ratio of 6:1 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 2", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0056] Example 3

[0057] 40.9g of methyltrimethoxysilane, 12.9g of hexamethyldisiloxane, 7.4g of tetramethyldivinyldisiloxane, 14.8g of octamethylcyclotetrasiloxane, 6.7ml of methanol, and 50ml of toluene were added to a flask, fully mixed and stirred, and the temperature of the mixed solution in the flask was reduced to 10°C. 32.4g of a 0.5%wt aqueous hydrochloric acid solution was added dropwise to the above flask using a constant pressure dropping funnel. The addition was completed in 100 minutes, and the temperature in the reaction flask was maintained at 10°C. The temperature was raised to 65°C and refluxed for 2h, then cooled to 25°C, allowed to stand for stratification, the lower acid water was separated, and the upper oil phase was removed from the system at 90°C and -0.095MPa to obtain MDT with a trifunctional branched structure ("M" and "D" have the same meanings as described above, and "T" represents the presence of "RSiO 3 / 2 " structured silicon-oxygen chain segments, where M / D / T = 24:20:30, some -Vi groups in the "M" chain segments replace -CH3 groups, and at the same time, 1 mol of MDT polysiloxane contains about 8 mol of hydroxyl active groups.) Polysiloxane: [CH3SiO 3 / 2 ]30 [Si(CH3)2O] 20 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemistry 5];

[0058] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0059] a:Vi(CH3)2SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 1];

[0060] b: [CH3SiO 3 / 2 ] 30 [Si(CH3)2O] 20 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemistry 5];

[0061] A: Add the above-mentioned [Chemical 1] and [Chemical 5] in a molar ratio of 8:1 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 3". The "branched polysiloxane polymer 3" is used as component A to prepare a high-adhesion, low-oiling silicone gel.

[0062] B: Add 27g of tetramethylcyclotetrasiloxane, 1.3g of tetramethyldisiloxane, 74g of octamethylcyclotetrasiloxane and 2.1g of concentrated sulfuric acid into a flask, stir and react at 25℃ for 5h, add 3.2g of sodium carbonate powder and stir to neutralize, filter out the insoluble solid powder, remove the low molecular weight in the filtrate from the system at 120℃ and -0.095MPa, and obtain a hydrogenated linear polysiloxane with 145 chain segments, dimethylhydrogensiloxy end-capping at both ends and 45 silicon-hydrogen chain segments in the middle: H(CH3)2SiO[Si(CH3)2] 100 [SiHCH3O] 45 Si(CH3)2H——[Chemical 6];

[0063] C: contains 5000ppm platinum-divinyltetramethyldisiloxane complex;

[0064] D: 2-methyl-3-butynyl-2-ol.

[0065] Mix A and B evenly, add D and mix evenly, then add C and mix evenly to obtain a high-adhesion and low-oiling silicone gel.

[0066] The peel strength, cone penetration and oil separation rate of high-bonding and low-oil separation silicone gel were tested according to the above test method. The specific addition amount and test results are shown in Table 1.

[0067] Example 4

[0068] Change the mass of hexamethyldisiloxane to 77.8g, and add the remaining substances in the same amount as in the experimental procedure [4] to obtain: [SiO2] 50 [Si(CH3)3O ½ ] 96 [OH]6——[Chemistry 7];

[0069] Add 500g of hydroxyl-terminated silicone oil to the reaction bottle, heat to 160℃, add 20ppm of KOH, stir and react under -0.095MPa negative pressure, stop heating and turn off the vacuum when the viscosity reaches 1800mPa·s. Add 20ppm of phosphoric acid and stir and neutralize for 30min to obtain hydroxyl-terminated linear polysiloxane: HO(CH3)2SiO[Si(CH3)2O] 300 Si(CH3)2OH——[Chemical 8];

[0070] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0071] a:Vi(CH3)2SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 1];

[0072] b: [SiO2] 50 [Si(CH3)3O ½ ] 96 [OH]6——[Chemistry 7];

[0073] c: HO(CH3)2SiO[Si(CH3)2O] 300 Si(CH3)2OH——[Chemical 8];

[0074] A: Add the above-mentioned [Chemical 1] [Chemical 7] [Chemical 8] in a molar ratio of 6:1:2 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 4", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0075] Example 5

[0076] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0077] a:Vi(CH3)2SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 1];

[0078] b: [CH3SiO 3 / 2 ] 30 [Si(CH3)2O] 20 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemistry 5];

[0079] c: HO(CH3)2SiO[Si(CH3)2O] 300 Si(CH3)2OH——[Chemical 8];

[0080] Preparation of the high-adhesion and low-oiling silicone gel:

[0081] A: Add the above-mentioned [Chemical 1] [Chemical 5] [Chemical 8] in a molar ratio of 8:1:2 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 5", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0082] Example 6

[0083] 1.86 g of tetramethyldivinyldisiloxane and 370 g of dehydrated octamethylcyclotetrasiloxane were added to a reaction bottle, heated to 110°C, 50 ppm of tetramethylammonium hydroxide was added, stirred for 4 h, heated to 150°C for 2 h, and low boiling products were removed from the system at -0.095 MPa to obtain a vinyl group-terminated linear polysiloxane with a chain number of 500: Vi(CH3)2SiO[Si(CH3)2O] 500 Si(CH3)2Vi——[Chemical 9];

[0084] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0085] a:Vi(CH3)2SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 1];

[0086] b: [SiO2] 50 [Si(CH3)3O ½ ] 35 [OH]6——[Chemical 4];

[0087] c:Vi(CH3)2SiO[Si(CH3)2O] 500 Si(CH3)2Vi——[Chemical 9];

[0088] A: Add the above-mentioned [Chemical 1] [Chemical 4] [Chemical 9] in a molar ratio of 6:1:1 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 6", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0089] Comparative Example 7

[0090] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0091] b: [CH3SiO 3 / 2 ] 30 [Si(CH3)2O] 20 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemistry 5];

[0092] c1: HO(CH3)2SiO[Si(CH3)2O] 300 Si(CH3)2OH——[Chemical 8];

[0093] c2:Vi(CH3)2SiO[Si(CH3)2O] 500 Si(CH3)2Vi——[Chemical 9];

[0094] Preparation of the high-adhesion and low-oiling silicone gel:

[0095] A: Add the above-mentioned [Chemical 5] [Chemical 8] [Chemical 9] in a molar ratio of 1:2:1 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 7", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0096] Comparative Example 8

[0097] 40.9g of methyltrimethoxysilane, 19.4g of hexamethyldisiloxane, 6.7ml of methanol and 50ml of toluene were added to the flask, mixed and stirred thoroughly, and the temperature of the mixed solution in the flask was lowered to 10°C. 32.4g of 0.5%wt hydrochloric acid aqueous solution was added dropwise to the above flask using a constant pressure dropping funnel. The addition was completed in 100 minutes, and the temperature in the reaction flask was kept at 10°C. The temperature was raised to 65°C and refluxed for 2h, then cooled to 25°C, allowed to stand for stratification, the lower acid water was separated, and the upper oil phase was removed from the system at 90°C and -0.095MPa to obtain a polysiloxane with the following structure: [CH3SiO 3 / 2 ] 30 [Si(CH3)3O ½ ] 24 [OH]5——[Chemical 10];

[0098] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0099] b: [CH3SiO 3 / 2 ] 30 [Si(CH3)3O ½ ] 24 [OH]5——[Chemical 10];

[0100] c1: HO(CH3)2SiO[Si(CH3)2O] 300 Si(CH3)2OH——[Chemical 8];

[0101] c2:Vi(CH3)2SiO[Si(CH3)2O] 500 Si(CH3)2Vi——[Chemical 9];

[0102] Preparation of the high-adhesion and low-oiling silicone gel:

[0103] A: Add the above-mentioned [Chemical 10] [Chemical 8] [Chemical 9] in a molar ratio of 2:1:1 into a four-necked bottle equipped with a thermometer and stirring, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 8", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0104] Example 9

[0105] Add 7.4g of hexamethylcyclotrisiloxane and 200g of anhydrous tetrahydrofuran to a dry flask, protect with nitrogen, and cool to 0°C. Add 50ml of methyl lithium (2M n-hexane solution) to the flask and keep the temperature at 0°C for 30 minutes. Dissolve 1480g of hexamethylcyclotrisiloxane in 1000ml of anhydrous tetrahydrofuran, add to the above flask, and react at 30°C for 5h. Add 6g of glacial acetic acid and react for 20min. Filter to remove insoluble salts. At 30°C and -0.095MPa, remove tetrahydrofuran from the system to obtain a single-end hydroxyl and single-end methyl polydimethylsiloxane product with a link number of 200: (CH3)3SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 11];

[0106] The mass of methyltrimethoxysilane was changed to 4.1 g, the mass of hydrochloric acid water was changed to 3.2 g, and the addition amounts of the remaining substances and the experimental steps were assimilated to [5] to obtain the following structure of polysiloxane: [CH3SiO 3 / 2 ]3[Si(CH3)2O] 20 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemical 12];

[0107] Add 500g of hydroxyl-terminated silicone oil to the reaction bottle, heat to 160°C, add 20ppm of KOH, stir and react under -0.095MPa negative pressure, stop heating when the viscosity reaches 60mPa·s, turn off the vacuum, add 20ppm of phosphoric acid and stir and neutralize for 30min to obtain hydroxyl-terminated linear polysiloxane: HO(CH3)2SiO[Si(CH3)2O] 50 Si(CH3)2OH——[Chemical 13];

[0108] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0109] a: (CH3)3SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 11];

[0110] b: [CH3SiO 3 / 2 ]3[Si(CH3)2O] 20 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemical 12];

[0111] c: HO(CH3)2SiO[Si(CH3)2O]50 Si(CH3)2OH——[Chemical 13];

[0112] A: Add the above-mentioned [Chemical 11], [Chemical 12], and [Chemical 13] in a molar ratio of 8:1:3 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 9", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0113] Example 10

[0114] The octamethylcyclotetrasiloxane was changed to 70.3 g, and the addition amount of the remaining substances and the experimental steps were assimilated to [5] to obtain the following structure of polysiloxane: [CH3SiO 3 / 2 ] 30 [Si(CH3)2O] 95 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemical 14];

[0115] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0116] a: (CH3)3SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 11];

[0117] b: [CH3SiO 3 / 2 ] 30 [Si(CH3)2O] 95 [Si(CH3)2ViO ½ ]8[Si(CH3)3O ½ ] 16 [OH]8——[Chemical 14];

[0118] c: HO(CH3)2SiO[Si(CH3)2O] 300 Si(CH3)2OH——[Chemical 8];

[0119] Preparation of the high-adhesion and low-oiling silicone gel:

[0120] A: Add the above-mentioned [Chemical 11] [Chemical 14] [Chemical 8] in a molar ratio of 8:1:2 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 10", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0121] Embodiment 11

[0122] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0123] a: (CH3)3SiO[Si(CH3)2O] 200 Si(CH3)2OH——[Chemical 11];

[0124] b: [SiO2] 30 [Si(CH3)2O] 20 [Si(CH3)3O ½ ] 24 [OH]5——[Chemistry 2];

[0125] c:Vi(CH3)2SiO[Si(CH3)2O] 500 Si(CH3)2Vi——[Chemical 9];

[0126] Preparation of the high-adhesion and low-oiling silicone gel:

[0127] A: Add the above-mentioned [Chemical 11] [Chemical 2] [Chemical 9] in a molar ratio of 5:1:3 into a four-necked bottle equipped with a thermometer and a stirrer, and the subsequent experimental steps are the same as those in Example 1 to obtain "branched polysiloxane polymer 11", which is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0128] Example 12

[0129] The structures of components A, B and C are the same as those in Example 1. Component D is 3,5-dimethyl-1-hexynyl-3-ol. The addition amount and test results are shown in Table 1.

[0130] Embodiment 13

[0131] The structures of components A, B and C are the same as those in Example 1. Component D is a mixture of 2-methyl-3-butynyl-2-ol and 3-methyl-1-ethynyl-3-ol in a mass ratio of 1:1. The addition amount and test results are shown in Table 1.

[0132] Embodiment 14

[0133] The amount of hexamethylcyclotrisiloxane added was changed to 6660 g, and the amount of the remaining substances and the reaction steps were the same as the preparation method [1] to obtain a polysiloxane with the following structure: Vi(CH3)2SiO[Si(CH3)2O] 900 Si(CH3)2OH——[Chemical 15];

[0134] Add 15.2g of methyl orthosilicate, 5.7g of hexamethyldisiloxane, 14.8g of octamethylcyclotetrasiloxane, 5.7ml of methanol, and 40ml of toluene to a flask, mix and stir thoroughly, and lower the temperature of the mixed solution in the flask to 10°C. Use a constant pressure dropping funnel to drop 14.4g of 0.5%wt hydrochloric acid aqueous solution into the above flask, and add it dropwise for 100 minutes. Keep the temperature in the reaction flask at 15°C. Heat to 65°C and reflux for 2h, cool to 25°C, stand for stratification, separate the lower acid water, and remove the low-boiling substances from the system at 90°C and -0.095MPa for the upper oil phase to obtain a polysiloxane with the following structure: [SiO2] 10 [Si(CH3)2O] 20 [Si(CH3)3O ½ ]7[OH] 20 ——[Chemistry 16];

[0135] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0136] a:Vi(CH3)2SiO[Si(CH3)2O] 900 Si(CH3)2OH——[Chemical 15];

[0137] b: [SiO2] 10 [Si(CH3)2O] 20 [Si(CH3)3O ½ ]7[OH] 20 ——[Chemistry 16];

[0138] Preparation of the high-adhesion and low-oiling silicone gel:

[0139] A: Add [Chemical 15] and [Chemical 16] in a molar ratio of 20:1 into a four-necked bottle equipped with a thermometer and a stirrer, heat to 150°C, add 40ppm of KOH catalyst, react under vacuum for 4h, add 40ppm of phosphoric acid, stir and neutralize for 1h, and obtain "branched polysiloxane polymer 1", which is used as component A to prepare high-bonding and low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0140] Embodiment 15

[0141] Preparation method of single-end hydroxyl single-end vinyl polysiloxane: Add 8.6g of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane and 200g of anhydrous tetrahydrofuran to a dry flask, protect with nitrogen, and cool to 0°C. Add 50ml of methyl lithium (2M n-hexane solution) to the flask and keep it at 0°C for 30min. Dissolve 2960g of hexamethylcyclotrisiloxane and 136.2g of 2,4,6-trimethyl-2,4,6-triphenylcyclotrisiloxane in 500ml of anhydrous tetrahydrofuran, mix them evenly, add them to the above flask, and react at 30°C for 5h. Add 6g of glacial acetic acid and react for 20min. Filter to remove insoluble salts. At 30°C and -0.095 MPa, tetrahydrofuran was removed from the system to obtain a polysiloxane product with the following structure: Vi(CH3)2SiO[SiCH3PhO] 10 [Si(CH3)2O] 400 Si(CH3)2OH——[Chemical 17].

[0142] Add 68.5g of methyl orthosilicate, 16.2g of hexamethyldisiloxane, 14.8g of octamethylcyclotetrasiloxane, 6.81g of 2,4,6-trimethyl-2,4,6-triphenylcyclotrisiloxane, 8.5ml of methanol, and 70ml of toluene to a flask, mix and stir thoroughly, and lower the temperature of the mixed solution in the flask to 10°C. Use a constant pressure dropping funnel to drop 64.8g of a 1.0%wt hydrochloric acid aqueous solution into the above flask, and add the solution dropwise for 100 minutes, keeping the temperature in the reaction flask at 15°C. Heat to 65°C and reflux for 2h, cool to 25°C, stand for stratification, remove the lower acid water, and remove the low-boiling substances from the system at 90°C and -0.095MPa to obtain a polysiloxane with the following structure: [SiO2] 45 [SiCH3PhO]5[Si(CH3)2O] 20 [Si(CH3)3O ½ ] 20 [OH] 40 ——

Chemistry 18

[0143] Add 500g of hydroxyl-terminated silicone oil to the reaction bottle, heat to 160℃, add 20ppm of KOH, stir and react under -0.095MPa negative pressure, stop heating and turn off the vacuum when the viscosity reaches 100000mPa·s. Add 20ppm of phosphoric acid and stir and neutralize for 30min to obtain hydroxyl-terminated linear polysiloxane: HO(CH3)2SiO[Si(CH3)2O] 1600 Si(CH3)2OH——[Chemical 19];

[0144] A:Vi(CH3)2SiO[SiCH3PhO]10 [Si(CH3)2O] 400 Si(CH3)2OH——[Chemical 17];

[0145] b: [SiO2] 45 [SiCH3PhO]5[Si(CH3)2O] 20 [Si(CH3)3O ½ ] 20 [OH] 40 ——

Chemistry 18

[0146] c: HO(CH3)2SiO[Si(CH3)2O] 1600 Si(CH3)2OH——[Chemical 19];

[0147] A: Add [Chemical 17] [Chemical 18] [Chemical 19] in a molar ratio of 40:1:1 into a four-necked bottle equipped with a thermometer and a stirrer, heat to 150°C, add 40ppm of KOH catalyst, stir and react for 4h under vacuum, add 40ppm of phosphoric acid, stir and neutralize for 1h, and obtain "branched polysiloxane polymer 1", which is used as component A to prepare high-bonding and low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1, and the addition amounts and test results are shown in Table 1.

[0148] Example 16

[0149] Add 8.6g of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane and 200g of anhydrous tetrahydrofuran to a dry flask, protect with nitrogen, and cool to 0°C. Add 50ml of methyl lithium (2M in n-hexane) to the flask and keep the temperature at 0°C for 30 minutes. Dissolve 74g of hexamethylcyclotrisiloxane in 500ml of anhydrous tetrahydrofuran, add to the above flask, and react at 30°C for 5h. Add 6g of glacial acetic acid and react for 20min. Filter to remove insoluble salts. At 30°C and -0.095MPa, remove tetrahydrofuran from the system to obtain a polysiloxane with the following structure: Vi(CH3)2SiO[Si(CH3)2O] 10 Si(CH3)2OH——[Chemical 20].

[0150] The mass of octamethylcyclotetrasiloxane was changed to 59.2 g, and the addition amount and preparation method of the remaining substances were the same as the preparation method of [Chemical 2] to obtain a polysiloxane with the following structure: [SiO2] 30 [Si(CH3)2O] 80 [Si(CH3)3O ½ ] 24 [OH]5——[Chemical 21];

[0151] The branched polysiloxane polymer is prepared by reacting the following raw materials:

[0152] a:Vi(CH3)2SiO[Si(CH3)2O] 10 Si(CH3)2OH——[Chemical 20];

[0153] b: [SiO2] 30 [Si(CH3)2O] 80 [Si(CH3)3O ½ ] 24 [OH]5——[Chemical 21];

[0154] A: Add the above-mentioned [Chemical 20] [Chemical 21] in a molar ratio of 5:1 into a four-necked bottle equipped with a thermometer and a stirrer. The subsequent experimental steps are the same as those in Example 1. The reaction product is used as component A to prepare a high-adhesion, low-oiling silicone gel. The structures of components B, C, and D are the same as those in Example 1. The addition amounts and test results are shown in Table 1.

[0155] Cone penetration test method: The cone penetration test is the needle penetration using a 1 / 4 cone as specified in JIS K2220, and the cone penetration test range is 10~110] using the automatic needle penetration meter RPM-101 manufactured by Rigo Co., Ltd.;

[0156] Sample preparation: Mix the above components evenly according to the proportion, put them into the cone penetration test barrel, vacuum degas for 5-10 minutes, heat and cure in an oven at 125℃ for 30 minutes, and cool to room temperature for testing.

[0157] Test method for peel strength: refer to FINAT test method FTM10;

[0158] Sample preparation: The mixed silicone gel composition was evenly coated on the PU film with a coating device, with a coating thickness of about 100μm, and heated in a 150℃ oven for 30min. After cooling to room temperature, several rectangular strips were cut according to the size of 20mm×200mm, and attached to a clean steel plate. A 2kg roller was used to roll back and forth twice at a speed of 10mm / s without pressure, and then a 20g / cm 2 Press with a steel bar, place at room temperature (22°C) for 20 hours, take it out and remove the steel bar.

[0159] Sample testing: Use a release force tester (AR-1500) to peel off the above sample at a speed of 0.3 m / min and a peeling angle of 180 degrees. The measured tensile force is the release force. The peeling speed ranges from low speed (0.3 m / min) to high speed (300.0 m / min).

[0160] Oil separation rate test method:

[0161] Place the silicone gel composition in a 125°C oven for 30 minutes of heating and curing, and then cool to room temperature. Accurately weigh about 100g of silicone gel cured film, spread it on glass fiber cloth (such as glass fiber cloth, non-woven fabric, oil-absorbing paper), and then place it in a 200°C oven for 48 hours. Remove the silicone gel sheet and weigh it accurately. The percentage of silicone oil in the weight difference before and after exudation to the total amount of silicone gel is used to determine the oil separation rate.

[0162] The peel strength, cone penetration and oil separation rate of high-bonding and low-oil separation silicone gel were tested according to the above test method. The specific addition amount and test results are shown in Table 1.

[0163] Table 1: Summary of test results

[0164] The effective platinum content of the platinum-containing catalyst is 5000ppm; the ratio of the molar content of vinyl to the molar content of hydrogen in the silicone gel component is calculated and added at a ratio of 1:0.8 to ensure the adhesion of the silicone gel.

[0165] From the test results of the embodiments and comparative examples, the polysiloxane having the branched structure shows good peeling force and softness; the oil separation rate of comparative examples 7 and 8 is higher than that of the embodiments of the present invention (the oil separation rate is set to ≤5%. When the oil separation rate is less than 5%, it meets the requirements, and when the oil separation rate is greater than 5%, it does not meet the requirements).

Claims

1. A branched polysiloxane polymer, characterized in that Prepared by the reaction of the following raw materials: a: Linear polysiloxane with a single-terminal hydroxyl structure; b: polysiloxane having a trifunctional or tetrafunctional branched structure; c: hydroxyl-terminated linear polysiloxane; The molar ratio of a, b and c is (3-50):1:(0-3); The general structural formula of a is: 1 1R 2 1CH3SiO[SiCH3R 2 1O] X1 [Si(CH3)2O] Y1 Si(CH3)2OH; The R 1 1 is any one of -Vi and -CH3; R 2 1 is any one of -CH3 and -Ph; X1 and Y1 are integers of 10-1000; The general structural formula of b is: 1 2] n SiO (4-n) / 2 ] q [SiCH3R 2 2O] X2 [Si(CH3)2R 1 2O ½ ] m1 [Si(CH3)2R 2 2O ½ ] m2 [OH] s ; The R 1 2 is any one of -Vi, -CH3, -OCH3; R 2 2 is any one of -CH3 and -Ph; X2 is an integer of 0-100, n is an integer of 0 or 1; m1 and m2 are integers of 0-100; q and s are integers of 5-50; The R 1 1. R 1 At least one of the 2 is -Vi.

2. The branched polysiloxane polymer according to claim 1, characterized in that The R 2 1 is -CH3; X1 and Y1 are integers of 10-500.

3. The branched polysiloxane polymer according to claim 1, characterized in that The R 1 2 is any one of -Vi and -CH3, wherein R 2 2 is -CH3; X2 is an integer of 0-50, m1 and m2 are integers of 1-50, and q and s are integers of 5-30.

4. The branched polysiloxane polymer according to claim 1, characterized in that The general structural formula of c is: 3 (CH3)2SiO[Si(CH3)2O] X3 Si(CH3)2R 3 ; The R 3 is -OH, and X3 is an integer of 50-1600.

5. The branched polysiloxane polymer according to claim 4, characterized in that The X3 is an integer of 100-600.

6. The branched polysiloxane polymer according to claim 1, characterized in that The preparation method of the branched polysiloxane polymer is as follows: a, b and c are put into a reaction container, the temperature is increased, an alkali glue is added to react, and then an acid glue is added to neutralize to obtain the branched polysiloxane polymer.

7. A method for preparing a high-adhesion, low-oiling silicone gel using the branched polysiloxane polymer according to any one of claims 1 to 6, characterized in that: Prepared by the reaction of the following raw materials: A: branched polysiloxane polymer; B: organohydrogenpolysiloxane; C: platinum catalyst; D: inhibitor; The method for preparing the high-bonding and low-oiling organic silicone gel comprises the following steps: mixing A and B evenly, adding D and mixing evenly, and then adding C and mixing evenly to obtain the high-bonding and low-oiling organic silicone gel.

8. The method for preparing high-adhesion and low-oiling silicone gel according to claim 7, characterized in that: The inhibitor is one of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol or 3,5-dimethyl-1-hexynyl-3-ol, or a mixture of more than one thereof.

Citation Information

Patent Citations

  • Low-temperature-resistant transparent silica gel composition for liquid crystal touch screen filling

    CN109266010A

  • Low-viscosity high-strength toughened silicon resin composition and preparation method thereof

    CN112280044A